O impacto da pandemia de COVID-19 na mudança de comportamento relacionado ao exercício físico: adesão ao ciclismo - Menezes, Rosineide Mota (2023)
Introduction: The Covid-19 pandemic brought about a change in the daily routines of the majority of the population, particularly regarding physical exercise. There was a significant reduction in levels of moderate and high-intensity exercise, which could have negative effects on people's physical and mental health. To overcome these effects, the World Health Organization (WHO) recommended engaging in physical exercises that could be practiced outdoors, as long as physical and social distancing measures were adhered to. Among the exercises, cycling stands out due to its numerous benefits for physical and mental health, and there has been an exponential increase in the number of cyclists during the pandemic. Therefore, the aim of this study is to analyze the reasons for adopting cycling as a form of physical exercise before and during the pandemic, assess possible changes in motivations between the two periods, and compare adherence to cycling between genders and according to the weekly distance traveled. Method: This is a quantitative crosssectional observational descriptive study. The sample consisted of 201 individuals who practiced cycling as a form of physical exercise. Data collection involved the use of a sociodemographic questionnaire and the Inventory of Motivation for Regular Physical Activity (IMPRAF-54). Data were analyzed using SPSS 25, including the Kolmogorov-Smirnov normality test, Student's T-test, and One-Way ANOVA with Tukey's post hoc test. The adopted significance level was p<0.05. Results: Health and pleasure were the primary motivations for cycling both before and during the pandemic, for both men and women. However, before the pandemic, women were more motivated by aesthetics, health, and pleasure compared to men during the same period. During the pandemic, women were more motivated by pleasure and stress control compared to men. When analyzing the number of kilometers cycled per week, it was evident that all groups (up to 100 km, between 101 km and 200 km, and above 200 km) were primarily motivated by health and pleasure. However, when comparing motivations within the groups, it was observed that before the pandemic, the group cycling longer distances (above 200 km) was more motivated by competitiveness. During the pandemic, there was a difference in the stress control dimension, which motivated the group cycling shorter distances (up to 100 km) more. Conclusion: Health and pleasure are the main motivations for adopting cycling as a form of physical exercise, regardless of the period, gender, or the cyclist's weekly distance traveled.